The Use of Market Mechanisms in Higher Education Finance and State Control: Ontario Considered - Young, Stacey J. (Canadian Journal of Higher Education, 2002)
Marketization has been so liberally applied to understanding higher education finance policy change that it has become a less potent conceptual tool. Through its evolution as a conceptual tool, the relationship between state control and market control has become an either/or proposition. In Ontario, state control over higher education has been strengthened with the use of market mechanisms, particularly as they have been utilized in resource allocation. This article outlines seven major higher education policy changes that make use of market mechanisms while enhancing state control. It is argued that marketization is a compromise between privatization, academic autonomy, and blatant state control in the face of the backlash against government intrusion in western socio- economic life.